2008
DOI: 10.1107/s1600536808004467
|View full text |Cite
|
Sign up to set email alerts
|

Poly[triaquabis(μ2-3-carboxypyrazine-2-carboxylato)dilithium(I)]

Abstract: Key indicators: single-crystal X-ray study; T = 295 K; mean (C-C) = 0.003 Å; R factor = 0.052; wR factor = 0.144; data-to-parameter ratio = 11.3.In the title compound, [Li 2 (C 6 H 3 N 2 O 4 ) 2 (H 2 O) 3 ] n , the coordination number for both independent Li + cations is five. One of the Li + ions has a distorted trigonal-bipyramidal geometry, coordinated by one of the carboxyl O atoms of a 3-carboxypyrazine-2-carboxylate ligand, two O atoms from two water molecules, and an N and a carboxylate O atom of a seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 27 publications
2
18
0
Order By: Relevance
“…For the crystal structures of two Li I complexes with a pyrazine-2,3-dicarboxylate ligand, see: Tombul et al (2008); Tombul & Gü ven (2009). For the crystal structure of a Li I complex with a pyrazine-2,3,5,6-tetracarboxylate ligand, see: Starosta & Leciejewicz (2010) and a pyrazine-2,5-dicarboxylate ligand, see: Starosta & Leciejewicz (2011).…”
Section: Related Literaturementioning
confidence: 99%
“…For the crystal structures of two Li I complexes with a pyrazine-2,3-dicarboxylate ligand, see: Tombul et al (2008); Tombul & Gü ven (2009). For the crystal structure of a Li I complex with a pyrazine-2,3,5,6-tetracarboxylate ligand, see: Starosta & Leciejewicz (2010) and a pyrazine-2,5-dicarboxylate ligand, see: Starosta & Leciejewicz (2011).…”
Section: Related Literaturementioning
confidence: 99%
“…For pyrazine-2,3-dicarboxamide, four Cu II structures (Mondal & Ray, 1977;Klein et al, 1983) with the ligand in an N,O-chelating mode and one Ag I structure (Massoud et al, 2009) with the ligand in an N:N 0 -bridging mode have been reported. In contrast, many compounds of pyrazine-2,3-dicarboxylic acid with alkali (Tombul et al, 2006(Tombul et al, , 2007Tombul, Gü ven & Bü yü kgü ngö r, 2008;Tombul, Gü ven & Svoboda, 2008;Tombul & Guven, 2009) and transition metals (Zou et al, 1998(Zou et al, , 1999Konar et al, 2004;Xu et al, 2008) have been synthesized and structurally characterized.…”
Section: Commentmentioning
confidence: 99%
“…In all of them, Li coordination is trigonal bipyramidal (Tombul et al, 2008), (Tombul & Güven, 2009), (Starosta & Leciejewicz, 2011), (Starosta & Leciejewicz, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…For the structures of lithium complexes with pyrazine-2,3-dicarboxylate ligands, see : Tombul et al (2008); Tombul & Gü ven (2009) ;Starosta & Leciejewicz (2011. The structure of 5,6-dimethylpyrazine-2,3-dicarboxylic acid dihydrate was reported by Vishwershwar et al (2001).…”
Section: Related Literaturementioning
confidence: 99%